Pathophysiology of urinary incontinence. Issue 4 (April 2020) - Wyndaele, Michel; Hashim, Hashim
Abstract: Urinary incontinence, or the complaint of involuntary loss of urine, is a debilitating condition of the lower urinary tract with a potentially significant impact on a patient's physical and mental wellbeing and on their functioning and place in society. Due to the high prevalence of this disorder, the economic burden on healthcare systems worldwide is enormous. Urinary incontinence has a high prevalence in women, but men can be affected as well after a radical prostatectomy or when suffering from chronic urinary retention. Stress, urgency and mixed urinary incontinence are the most common types of urinary incontinence, but other types exist as well. The pathophysiological mechanisms behind these different types of urinary incontinence have been studied extensively. New insights allow for the development of improved diagnostic and therapeutic strategies and ultimately in the reduction of the potentially devastating impact of urinary incontinence on an individual patients' quality of life. In this review, we explore the current theories on the mechanisms behind urinary incontinence.